Leveraging the modular design approach to enhance variation of SME LORI jewelry - Morinta Rosandini; Dewi Isma Aryani; Elliati Djakaria; Riana Plourida Hura; Nadiah Salsabila; Jeng Oetari; Prafitra Viniani; Roro Retno Wulan (International Journal of Visual and Performing Arts, 2023)
LORI SME (Small and Medium Enterprise), operating as a producer of fashion accessories characterized by local craftsmanship, encounters challenges in accommodating diverse customer preferences due to resource constraints. To unleash its full potential, there exists a pressing need to adopt innovative design methodologies. This research endeavors to investigate the application of a modular design approach as a strategic solution for augmenting the variety of LORI SME accessories, thereby facilitating the creation of a range of jewelry products that can be easily tailored and adapted to meet individual customer requirements. The study utilizes a qualitative research methodology, encompassing literature reviews, interviews with the owner, exploration of visual motifs and materials, and practice-based research. The findings of this research illuminate that the adoption of a modular design approach significantly enhances the diversity of LORI SME's jewelry offerings, particularly in the case of its necklace products. This modular approach provides SMEs with a broader array of customizable necklace options characterized by distinctive local motifs and high craftsmanship value. These findings furnish valuable insights for SMEs within the LORI SME sector aiming to expand their product portfolios. Additionally, they offer guidance to designers and artisans regarding the potential advantages and challenges associated with the incorporation of modular design strategies in the broader context of small business innovation and product development.